Optimum number of units to minimize the construction cost of multi-story buildings - Alver, G; Biçer, Ü (WIDE DREAMS PROJECTOS MULTIMEDIA LDA, 2002)
In the architectural design of multi-story buildings, the number of units Per floor is dependent on the lot definition, necessities, legal regulations, and architectural designs. However, the cost of the number of the units on a floor must be factored in. In this study, construction cost of units per floor has been researched and optimum number of units Per floor has been calculated. Unit prices for area have been calculated from sample floor plans to obtain an optimum number of units Per floor of the multi-story building. On the sample floor plans, units have been created by analyzing the minimum. living space from a specified module system. After comparing five different floor plans to minimize the common use and circulation spaces, Optimum Number of Units to Minimize the Construction Cost of Multi-Story Buildings was determined. As a result of this, this optimum value will probably be useful to construction cost in general habitations.
Keywords: multi-story buildings; number of units; the external wall costs for Per units; Architecture; Construction & Building Technology; Engineering; Environmental Sciences & Ecology; Urban Studies